Trichloroethylene and trichloroethanol induce skin sensitization with focal hepatic necrosis in guinea pigs. Issue 1 (15th August 2020) - Zhao, Na; Song, Xiangrong; Naito, Hisao; Li, Hongling; Huang, Yongshun; Liu, Lili; Lu, Fengrong; Cai, Tingfeng; Ito, Yuki; Kamijima, Michihiro; Huang, Hanlin; Nakajima, Tamie; et al.
Abstract: Objectives: Occupational exposure to trichloroethylene (TCE) induces trichloroethylene hypersensitivity syndrome (TCEHS), which causes hypersensitivity dermatitis and hepatitis. However, whether TCE itself or its two metabolites, trichloroethanol (TCEOH) and trichloroacetic acid (TCA), are involved in TCEHS remains unclear. Therefore, in this study we explored the allergens causing TCEHS and characterized TCEHS‐related liver injury in guinea pigs. Method: The guinea pig maximization test was performed using TCE, TCEOH, and TCA as candidate allergens. Skin inflammation was scored, and liver function and histopathological changes were evaluated by biochemical tests and hematoxylin and eosin staining, respectively. Results: The sensitization rates for TCE, TCEOH, and TCA were 90.0%, 50.0%, and 0.0%, respectively. In the TCE and TCEOH experimental groups, the skin showed varying degrees of erythema with eosinophil granulocyte infiltration in the dermis. Additionally, serum alanine aminotransferase and γ‐glutamyl transpeptidase levels increased significantly, and histological analysis revealed focal hepatocellular necrosis with inflammatory cell infiltration in the liver. Conclusions: TCE is the main cause of allergy and TCEOH is a secondary factor for allergy in guinea pigs. TCE and TCEOH can cause immune‐mediated skin sensitization complicated by focal hepatic necrosis.